MACIÇO DA TIJUCA, SUAS FLORESTAS E O METABOLISMO SOCIAL DA CIDADE DO RIO DE JANEIRO, BRASIL, DO SÉCULO XIX AO INÍCIO DO XX - Sales, Gabriel Paes da Silva; Guedes-Bruni, Rejan R. (Mercator, 2026)
The landscape of Rio de Janeiro, characterized by its unique geomorphological configuration and the diversity of its forests and ecosystems, reflects the historical process of the city’s formation. This study examines the role of the Tijuca Massif in urban expansion, particularly during the 19th century, identifying the main factors that guided land use and transformation in a dynamic process that continues to resonate today. The massif and the Tijuca Forest—the largest planted urban forest in Brazil, resulting from an innovative 19th-century project—functioned as structuring vectors for the city, influencing both territorial expansion and the development of cultural practices and ways of life that shape Carioca identity. The presence of green spaces in the heart of the metropolis transcends their natural heritage value, revealing dimensions that are not only biological but also cultural and historical, which reframe their significance. Accordingly, the city can be understood as a dynamic organism in constant interaction with the biophysical environment, in which urban transformations reflect a network of social, ecological, and political interactions, with the massif and its forests occupying a central role as an expression of this socio-environmental metabolism.